(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
A simple, accurate UV-VIS Spectrophotometric method has been developed using a dissolution media, Tween 20 (0.15%) as a solvent to determine the Triamcinolone. At predetermined λmax of 240 nm, method was proved linear in the range of 10-50 µg/ml with good correlation coefficient (R2= 0.998) and excellent recovery (between 98 and 101%). This method was successfully applied to the determination of Triamcinolone from dissolution media, 0.15% Tween 20 aqueous solution. This method can be employed for the dissolution study of Triamcinolone in injectable suspension.